Bringing ROS to agriculture automation: Hardware abstraction of agriculture machinery - Hajjaj S.S.H.; Sahari K.S.M. (Research India Publications, 2023)
Concerns over food security in recent years have led to increased interest in agriculture automation, researchers around the world are looking for new and innovative ways to automate agriculture and improve its efficiency. Some researchers attempt to automate existing agriculture machinery, while others attempt to introduce robotics into agriculture, with both approaches have merit and potential. However, agriculture automation brings about vast engineering challenges; networking over wide open fields, navigation over rough soil, localization in a field of greenery, image processing hampered by loss of illumination due to weather, etc. and due to these challenges, agriculture automation remain impractical and uneconomical. The Robot Operating System (ROS) offers potential solutions to these challenges, and when combined with other open-source technologies, such as android or IoT, the potential is even higher. But before these benefits could be realized, agriculture machinery and robots must be made ROS-ready. This paper outlines and discusses the hardware/software steps needed to achieve exactly that. First by detailing the processing of making existing agriculture machinery ROS-ready, then by detailing the process of modifying ROS-ready robots to perform Agriculture tasks. The procedure is discussed in details with real examples, and references to ROSs resources and material. Taking another step closer towards implementing practical agriculture automation Research India Publications.